A Study on The Determination of Some Morphological and Physiological Characteristics of Common Vetch (Vicia sativa L.) Seeds - DUMANOĞLU, Zeynep; ÇAÇAN, Erdal; KÖKTEN, Kağan (MAS Journal of Applied Sciences, 2022)
This study was carried out to determine some morphological and physiological characteristics of common vetch seeds. The study was carried out in the laboratories of Bingöl University, Faculty of Agriculture, Biosystem Engineering and Field Crops departments in 2019-2020. The common vetch Altınoğlu-2001, Aneto, Ankaramoru08, Cumhuriyet-99, Orakefe and Tamkoç-2000 varieties were used as plant material. Morphological features of common vetch seeds are length (mm), width (mm), surface area (mm2 ), mean arithmetic diameter (mm), mean geometric diameter (mm), sphericity and thousand seed weight (g), and physiological features are germination rate. (%), germination time (day), mean root (cm) and shoot (cm) lengths were considered. Average length of seeds of common vetch cultivars was 4.876 mm, width was 4.403 mm, surface area was 17.808 mm2, arithmetic diameter was 4.639 mm, geometric diameter was 35,599 mm, sphericity value was 7.219 and thousand-grain weight was 58.050 g. In terms of these characteristics, Orakefe variety gave the highest values, while Cumhuriyet-99 gave the lowest values. Average germination rate of seeds of common vetch cultivars was 99.167%, germination time was 1.060 days, shoot length was 7.123 cm and root length was 5.794 cm. The longest shoot length was determined in Cumhuriyet-99 and the shortest shoot length was determined in Orakefe cultivars. The longest root length was determined in Ankaramoru08, and the shortest root length was determined in the Altınoğlu-2001 variety.